2020
DOI: 10.7249/rr3254
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Look at Military and Civilian Pay Levels and Recruit Quality

Abstract: Limited Print and Electronic Distribution RightsThis document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Our approach involved using military personnel and pay data provided by the Defense Manpower Data Center (DMDC), active duty personnel survey data provided by DoD's Office of People Analytics, and Current Population Survey data from the Bureau of Labor Statistics. Our analysis builds on and extends previous studies that have computed RMC percentiles (Hosek, Asch, and Mattock, 2012;Hosek et al, 2018;Smith, Asch, and Mattock, 2020) and the Hosek, Asch, and Mattock (2012) study that computed the DECI and compared it with the ECI.…”
Section: Figures IXmentioning
confidence: 76%
See 3 more Smart Citations
“…Our approach involved using military personnel and pay data provided by the Defense Manpower Data Center (DMDC), active duty personnel survey data provided by DoD's Office of People Analytics, and Current Population Survey data from the Bureau of Labor Statistics. Our analysis builds on and extends previous studies that have computed RMC percentiles (Hosek, Asch, and Mattock, 2012;Hosek et al, 2018;Smith, Asch, and Mattock, 2020) and the Hosek, Asch, and Mattock (2012) study that computed the DECI and compared it with the ECI.…”
Section: Figures IXmentioning
confidence: 76%
“…Recent RAND analysis has considered how military and civilian pay compared in more recent years (Smith, Asch, and Mattock, 2020). Our study of RMC percentiles for 2017 found that RMC was at the 85th percentile of the civilian wage distribution for enlisted personnel and at the 77th percentile of the civilian wage distribution for officers (Smith, Asch, and Mattock, 2020).…”
Section: Background On Rmc Percentiles and The Ecimentioning
confidence: 80%
See 2 more Smart Citations
“…To overcome this limitation, we used a common substitute, years of potential experience, which is calculated as the difference between an individual's age and an assumed age at the time they completed their education (as measured before our recategorization). In other words, years of potential experience is calculated as age minus 18 years for high school graduates or high school dropouts, age minus 20 years for those with some college or associate's degrees, age minus 22 years for college graduates, and age minus 24 years for those with advanced degrees (Smith, Asch, and Mattock, 2020). The resulting number is the presumed number of years the individual has been in the workforce.…”
Section: Identifying a Sample Of Civilians In The Dod Cyber Workforce...mentioning
confidence: 99%